THE INFLUENCE OF LIFE STYLE, SOCIAL MEDIA, PROMOTIONS AND PRICE ON IMPLUSIVE BEHAVIOR BUYING OF GEN-Z SHOPEE USERS PAYLATER IN SEMARANG - Avilla Rahma Maulana; Septian Yudha Kusuma; Nina Woelan Soebroto (Journal of Management and Innovation Entrepreneurship (JMIE), 2025)
This study aims to analyze the influence of lifestyle, social media, promotions, and price on the impulsive buying behavior of Gen-Z Shopee Paylater users in Semarang City. The research method used is a quantitative approach with a causal research design. The sample in this study consisted of 100 Gen-Z respondents who have used Shopee Paylater, selected using a purposive sampling technique. Data were collected through questionnaires distributed online and analyzed using multiple linear regression with SPSS version 26.0 for Windows. The results of the study show that lifestyle, social media, and promotions partially have a significant effect on impulsive buying behavior, while price does not have a significant effect. Simultaneously, these four variables influence impulsive buying behavior by 72.2%, while the remaining 27.8% is influenced by other variables not examined in this study. The conclusion of this research indicates that lifestyle, social media, and promotional factors are the main drivers of impulsive buying behavior among Gen-Z Shopee Paylater users, while price is not a determining factor in their impulsive purchasing decisions.